Penerapan Konseling Kelompok Teknik Self Management untuk Mengurangi Perilaku Terlambat Datang ke Sekolah - Irawan, Teguh; Mutakin, Fakhruddin; Ernawati, Sitti (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2024)
Study on the Use of Self-Management Strategies in Group Counseling to Reduce Late Arrival Behavior for Class XI BIMA SMA Students: 10 students out of 36 were chosen at random to serve as the sample for this research. Tests, interviews, and observation are used as data collection techniques. and data reduction, data display, and conclusion-drawing using the Miles & Huberman methodology. Of the 10 research subjects, it can be said that all subjects experienced a significant decrease in the overall score obtained by students in pre-research of 850 in the High category, then experienced a decrease to 662 in the Medium category in cycle I, and in cycle II again experienced a good decrease. obtained 422 into the Low category. So from the score obtained, the ten research subjects from pre-research to cycle II above, showed 100% reaching or even exceeding the success indicator, namely 70%. And these outcomes show that using group counseling along with self-management strategies can effectively reduce the behavior of students arriving late to class.